2021
DOI: 10.1007/s11356-021-13127-x
|View full text |Cite|
|
Sign up to set email alerts
|

Where is the gray side of green growth? Theoretical insights, policy directions, and evidence from a multidimensional approach

Abstract: Addressing the geographical relocation of the pollution-intensive gray side of low-carbon green production, our study analyzes potential determinants of green and gray growth performance of industrialized/developed countries (IDCs) and industrializing/ emerging economies (IEEs) over the 1996-2015 period. We define green growth by low-carbon output, while we link gray growth to comparative advantages of pollution havens. Green and gray growth models include such predictors as domestic income and foreign direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 90 publications
0
4
0
1
Order By: Relevance
“…In a similar study, Khan et al ( 2021 ) found that FDI inflows can lead to an acceleration of green economic growth, but this depends on transparent and relevant policies and regulations related to FDI and green growth progress. Demiral and Demiral ( 2021 ) employed a multidimensional approach to study the stimulators of green growth. One of the main findings of their study is that FDI can be considered as a motivator of green growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar study, Khan et al ( 2021 ) found that FDI inflows can lead to an acceleration of green economic growth, but this depends on transparent and relevant policies and regulations related to FDI and green growth progress. Demiral and Demiral ( 2021 ) employed a multidimensional approach to study the stimulators of green growth. One of the main findings of their study is that FDI can be considered as a motivator of green growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, according to the PHH (Demiral and Demiral 2021), firms operating in highly emission‐intensive and energy‐dependent sectors in the European countries may be carrying their emission‐intensive activities to other (developing) countries with relatively lenient environmental regulations. The increase of emissions in the trade partners may come back to Europe through its imports from outside the European periphery.…”
Section: Assessment Of Environmental Performance In Europementioning
confidence: 99%
“…As these products are more carbon‐intensive, international trade will deteriorate the environmental quality of developed countries (Georgiev and Mihaylov 2015). On the other hand, from the pollution haven hypothesis (PHH) aspect, the increasing liberalization enables (developed) countries with stringent environmental regulations to relocate their pollution‐intensive industries to environmentally‐unregulated partners that provide pollution havens (Cave and Blomquist 2008; Demiral and Demiral 2021). This mechanism is widely referred to as carbon leakage and is usually quantified as the ratio of emission growth in trade and/or investment partners over domestic emission reduction (Naegele and Zaklan 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, globalization has progressed at an accelerating pace, with trade openness deepening particularly in the emerging markets of Asia and Africa (Demiral et al, 2022; Demiral & Demiral, 2021). As a result, the total volume of international trade has continued to increase, growing by 75% between 2000 and 2020 alone.…”
Section: Introductionmentioning
confidence: 99%